ANALISIS DAMPAK PENERAPAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) PADA EFISIENSI WAKTU TUNGGU DI POLIKLINIK ANAK - Ajie, Whisnu; Cahyanti, Naomi Dwi; Simbolon, Nadya Veronica (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Waiting time is one of standards in hospitals. A waiting time of more than 30 minutes in prescription retrieval can reduce patient satisfaction. The purpose of this study was to determine the effectiveness of waiting time for prescription services after the implementation of the Hospital Management Information System (SIMRS). This research is a type of sequential explanatory design, with a combination method between quantitative methods with statistical tests and qualitative methods with interviews with pharmacy officers who use the SIMRS in the pediatric polyclinic of four people who have met the criteria “have used SIMRS for 2 years”. The results obtained, the waiting time for prescription services at the pediatric polyclinic for general prescription concoctions has met the Permenkes standard ≤30 minutes and has decreased by 10.4 minutes after implementing SIMRS. While the results for non-recipe general prescriptions have met the Permenkes standard ≤15 minutes and have decreased by 2.1 minutes after implementing SIMRS. Based on hypothesis testing, it can be concluded that there is an increase in the effectiveness of waiting time for prescription services after SIMRS is implemented for both concoction and non concoction prescriptions by looking at the significance value of the statistical test 0.00 <0.05.